STANDAR OPERASIONAL PROSEDUR DAN PELAKSANAAN FLIGHT FOLLOWING DI PERUSAHAAN PENERBANGAN - Aditya Wardana; Racha Bismoyo; Abdul Ghafar (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of this study is to analyze and to overcome the pilot’s performance discrepancy. It is also aimed to make the performance in accordance with the notice of flight following, to analyze and to optimize the radio HF signal, which is used in flight following and monitoring.  This is a Quantitative Research. The data collection method used Field and Library research. Kartesius analysis was used to measure the conformity of the operational standard procedure towards the flight following implementation. The result of the X variable (Conformity Performance) shows the average computation of the assessment factors of Performance Conformity (X variable).  The standard value achieved is 3.15. The result of the Y variable (Interest Quality) shows the average computation of the assessment factors of Interest Quality (Y variable), which is 3.44. Furthermore, the congruency level of X and Y variables are 91.07%. Therefore, it is concluded that the level of congruency between the conformity performance and the interest has achieved a satisfactory interpretation value.